The evolving role of Bertholletia excelsa in Amazonia: contributing to local livelihoods and forest conservation - Kainer, Karen A.; Wadt, Lucia H. O.; Staudhammer, Christina L. (Desenvolvimento e Meio Ambiente, 2018)
In the last three decades, Brazil nut (Bertholletia excelsa) has emerged as a cornerstone species for Amazonia. This has gone hand-in-hand with the creation of extractive reserves, an alternative land use model to balance biodiversity conservation with rural development, whereby traditional forest residents are assigned legal responsibility for co-management of these reserves and their resources, including Brazil nut. The essential role of this species in conservation and local livelihoods has precipitated a shift from general exploitation to more conscious, intensive management. Drawing heavily on our more than 25 years of research in the Brazilian state of Acre and the larger body of B. excelsa research across the Amazon basin, we ask: (1) Are Brazil nut harvests sustainable in terms of fruit production patterns and resilience to nut (seed) collection? (2) In what ways might production be augmented and nut quality enhanced? We highlight that scientific evidence and local knowledge indicate that current levels of nut harvests are compatible with sustaining populations of B. excelsa and its key seed disperser, Dasyprocta spp. Rather than concentrating on the fate of most seeds produced, the more pressing risk to B. excelsa populations is survival of existing large trees. Moreover, ample knowledge indicates possible futures to increase productivity by protecting and improving conditions of these large trees. Cutting lianas from host tree crowns dramatically improves productivity over time. Additional promising ways to grow Brazil nut-rich forests include: (1) Search and map previously unharvested productive trees located beyond traditional collection trails, (2) Tend new recruits, particularly in abandoned swidden fallows, and (3) Conduct enrichment plantings to establish small-scale intensive groves. Upgraded drying, storage and processing have led to dramatic improvements in nut quality and market access over the last 30 years. The growing knowledge base and diverse management interventions examined help promote Brazil nut sustainability and maintain its critical role in conserving Amazonian forests.